2008
DOI: 10.1021/ef800087x
|View full text |Cite
|
Sign up to set email alerts
|

Slagging Characteristics during Residential Combustion of Biomass Pellets

Abstract: Limited availability of sawdust and planer shavings and an increasing demand for biomass pellets in Europe are pushing the market toward other, more problematic raw materials with broader variation in total fuel ash content and composition of the ash forming elements as well as in their slagging tendencies. The main objective in the present work was therefore to determine the influence of fuel−ash composition on residual ash and slag behavior. Twelve different biomass pellets were used: reed canary grass (two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(192 citation statements)
references
References 9 publications
11
177
0
4
Order By: Relevance
“…fluidised beds and possibly grate combustors rather than powder combustors. Comparison of slag formation tendency in grate combustion for the pelletised fuels used in this study (dark) and some other biomass fuels combusted in similar conditions in previous studies (white) [37]. DDGS 800 *) not analyzed due to fast defluidization during the experiment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…fluidised beds and possibly grate combustors rather than powder combustors. Comparison of slag formation tendency in grate combustion for the pelletised fuels used in this study (dark) and some other biomass fuels combusted in similar conditions in previous studies (white) [37]. DDGS 800 *) not analyzed due to fast defluidization during the experiment.…”
Section: Discussionmentioning
confidence: 89%
“…bottom ash and slag) was quantified after each experiment and the products were collected for analysis, described in section 2.6. A previous study has shown that the variation in the slag formation between replicate combustion experiments is minimal [37].…”
Section: Combustion Tests In a Fluidised Bedmentioning
confidence: 97%
“…Para controlar esto Francia establece dos tipos de pellets de biomasas mixtas que poseen características específicas para su posible comercialización (Tabla III). Con base en los niveles de cloro y azufre estos productos sólo pueden ser utilizados para la producción de energía en grandes industrias que puedan financiar los sistemas de tratamiento de los gases de salida sin perjudicar en gran medida la rentabilidad del proceso, aunque la gran cantidad de residuos agrícolas que poseen muchos países [34] hace de esta industria un nuevo tema de investigación que propone un futuro interesante una vez se superen estos problemas de emisiones.…”
Section: Pellets De Biomasas Mixtasunclassified
“…Con base en este proceso se lleva a cabo la mayor aplicación actual de los pellets, por la cual se genera energía térmi-ca para el calentamiento de espacios; y es sobre este tema que muchos científicos han llevado a cabo estudios dirigidos a evaluar la cantidad de emisiones generadas [35], formación de escorias que deriven en problemas de taponamiento de los quemadores residenciales [34] y la relación entre la ceniza producida con la composición de los pellets empleados [36].…”
Section: Procesos De Gasificaciónunclassified
“…In case of agrobiomass pellets, however, it is quite challenging to obtain pollutant emission as low as in case of wood pellets due to the fact that at temperatures of approx. 750 °C slag is produced, hampering furnace operation (Gible et al, 2008 andJuszczak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%